Konferensi Video sebagai Aplikasi Pertemuan Tatap Muka Daring: Preferensi Pengguna berdasarkan Pengujian Usabilitas - Astrid Wahyu Adventri Wibowo; Berty Dwi Rahmawati; Hasan Mastrisiswadi (Jurnal Sistem dan Manajemen Industri, 2021)
The global pandemic of Corona Virus Disease (Covid-19) that hit Indonesia since March 2020 has changed the face-to-face system from offline to online. Video Conference (VC) becomes an alternative choice for delivering material, both learning and working. VC is a technology that allows users to hold face-to-face meetings at their respective places simultaneously. Various VC apps are becoming increasingly popular these days, such as Google Meet, Zoom, Youtube, Webex, Skype, GoTo Meeting, and Big Blue Button (BBB). This study is intended to provide a usability test of VC applications (such as Zoom, Google Meet, and BBB) and provide recommendations for VC as an online conference media based on user preferences. The usability measurement technique used is the System Usability Scale (SUS) and the USE questionnaire. The results of this study show that Zoom has the highest usability value compared to Google Meet and BBB, Google Meet is ranked second and BBB is ranked third.